Competing Information Sources - Einhorn, Eti (The Accounting Review, 2018)
ABSTRACT This study analyzes corporate voluntary disclosures to the capital market in the presence of competing information sources, from which traders can subsequently obtain additional public and private information. The analysis demonstrates that the anticipated access of traders to additional information sources may significantly alter the voluntary disclosure strategy of firms. It may explain a deviation from the conventional full disclosure equilibrium to equilibrium with partial and selective disclosure. It may also lead to an untypical equilibrium shape, where any information content can be disclosed and can be withheld with a positive probability, and where the stock price reflects a pricing discount upon disclosure rather than in its absence. JEL Classifications: D82; G10; M41.